Spräktabu og tabuomräder i norsk - Kinal, Maciej (Folia Scandinavica Posnaniensia, 2007)
The aim of the article is to present the various aspects of language taboo in Norwegian. The author tries to account for the term "language taboo" and draw some kind of distinction between the primiive "taboo of fear", the evolving "taboo of delicacy" and "taboo of proriety" in modem Norwegian. The latter has a social background and ranges from statements with a slightly vulgar tinge to extremely offenive acts of verbal abuse regarded as Face Threatening Acts. Social taboos generally include the deity, sex, excretion and strangers. In the conclusions the author underlines that taboo in Norwegian remains a little explored area and suggests a possible approach to a comprehensive analysis of the phenomenon. Further research in this field seems to be a necessity and should comprise both the anthropological, semantic and functional aspects of taboo, both within the culture and the language.